The Synoptic Gospels and the Problem of Genre - Shuler, Philip L. (My University, 1976)
The single question to which this dissertation is addressed is: to what literary genre do the synoptic gospels belong? The question per se is not a new one; nor is it one which fails to generate scholarly interest from one generation to the next. Nevertheless, it is one which is lacking a satisfactory solution. The essential difficulty with a solution appears to be derived from two sets of data which may be expressed in paradoxical relationship to one another: 1) the synoptic gospels are narratives composed of traditions attributed to Jesus and preserved by the church, traditions which are so presented as to focus upon Jesus' person, and 2) the synoptic gospels appear to have no "biographical intent" (understood in contemporary terms as a primary intent to preserve an accurate, historical account of Jesus). The problem, therefore, is this: the synoptic gospels are in some sense "biographical", but they are not "biographies".
Our own approach to this question begins with a preliminary discussion of the nature of a literary genre. Our conclusion is that the concept itself is broader and more dynamic than contemporary New Testament scholarship has yet accepted. Then, following a brief presentation of presuppositions, the reconstruction and definition of a literary genre, which was current at the time the gospels were written (historical aspect of genre reconstruction) and which is an appropriate category for the synoptic narratives (descriptive aspect of genre), is set forth. This genre is initially referred to as laudatory biography and is later more specifically identified as "encomium" biography. Its existence is posited on the basis of the ancient dichotomy between history and some biographical counterpart: it is defined by reference to the rules of characterization which were codified in the rhetorical rules for the encomium.
The proposition is then tested by a discussion of the synoptic gospels and their affinities with the genre as set forth. The basis of this discussion is as new in this dissertation as is the proposed solution to the initial question of genre. After pointing out the weaknesses of establishing genre relationships by a comparison of one specific text with another, we discuss the affinities of, the synoptic gospels to the "encomium" biography in terms of genre characteristics: namely, topoi, literary techniques, and purposes.
The essential contribution of this thesis is that it presents a reasonable identity and definition for the synoptic gospels as literary wholes. It offers a historical explanation for the paradoxical character of these narratives of Jesus by providing the literary basis for the presentation of a praiseworthy person in a narrative form which was not composed primarily for the purpose of recording events. More important for the exegete, it provides an intelligible whole with which and through which the individual parts may be viewed. This contributes to the "exact" interpretation of the text. Finally, after having identified a proper literary genre which conveys certain meanings and presuppositions, the authenticity of the may now be addressed anew.
Keywords: Religion; Religion